Controllable drivers that influence tourists’ satisfaction and revisit intention to Semenggoh Nature Reserve: the moderating impact of destination image - Wei-Chiang, Chan; Wan Hashim, Wan Ibrahim; Lo, May Chiun; Abang Azlan, Mohamad; T., Ramayah; Chee-Hua, Chin (Taylor & Francis Online, 2021)
Ecotourism is a foremost promoted tourism product by the Malaysian government and significantly contributed to rural communities’ income. The objective of this study was to explore the empirical evidence of the relationships among service quality, satisfaction, and revisit intention to an ecotourism site in Sarawak, namely, Semenggoh Nature Reserve by considering the moderating effect of the destination image. A total of 157 international and domestic tourists who visited the Semenggoh Nature Reserve took part voluntarily in this study. WarpPLS 6.0 software was used to perform the Partial Least Squares Structural Equation Modeling and hypotheses testing. The results revealed that service quality was found to significantly and positively impacting satisfaction, whereas satisfaction was found to drive revisit intentions. Additionally, the destination image was found to have a significant positive impact on tourist’s satisfaction. The study further revealed that the destination image does not enhance the relationship between satisfaction and revisit intention.